Phase analysis on the error scaling of entangled qubits in a 53-qubit system - Wei-Jia Huang (Nature Portfolio, 2021)
Abstract We have studied carefully the behaviors of entangled qubits on the IBM Rochester with various connectivities and under a “noisy” environment. A phase trajectory analysis based on our measurements of the GHZ-like states is performed. Our results point to an important fact that entangled qubits are “protected” against environmental noise by a scaling property that impacts only the weighting of their amplitudes. The reproducibility of most measurements has been confirmed within a reasonably short gate operation time. But there still are a few combinations of qubits that show significant entanglement evolution in the form of transitions between quantum states. The phase trajectory of an entangled evolution, and the impact of the sudden death of GHZ-like states and the revival of newly excited states are analyzed in details. All observed trajectories of entangled qubits arise under the influences of the newly excited states in a “noisy” intermediate-scale quantum (NISQ) computer.